In search of excellence : exemplary forest management in Asia and the Pacific - Durst, Patrick B.; FAO Regional Office for Asia and the Pacific; Regional Community Forestry Training Center for Asia-Pacific (Bangkok, Thailand); Asia-Pacific Forestry Commission (Bangkok : Food and Agriculture Organization of the United Nations, Regional Office for Asia and the Pacific : Regional Community Forestry Training Center for Asia and the Pacific, 2005)
Contributed articles.
At head of title: Asia-Pacific Forestry Commission.
Includes bibliographical references.
Keywords: Forest management -- Pacific Area; Forest management -- Asia